The Impact of Transformational Leadership on Knowledge Sharing: A Conceptual Framework - Zhang, Hui; Choi, Sang Long (Business Management and Strategy, 2024)
Knowledge is the most valuable asset for organizations seeking sustainable competitive advantage. Thus, knowledge sharing is essential to maintaining an organization’s productivity and performance. This paper explores the dimensions of transformational leadership to promote knowledge sharing to examine leaders’ behaviors in organizations. This paper discussed new combined transformational leadership with six dimensions: idealized influence, inspirational motivation, intellectual stimulation, individualized consideration, empowerment, and personal recognition. These dimensions have the potential to influence knowledge sharing. By drawing on various previous studies, the paper constructs a conceptual framework and formulates six propositions to further address the impact of transformational leadership on knowledge sharing within organizations.